2016
DOI: 10.4103/0970-9290.179834
|View full text |Cite
|
Sign up to set email alerts
|

Influence of working length and foraminal enlargement on foramen morphology and sealing ability

Abstract: Under the conditions of this study, it can be concluded that foramen enlargement resulted in more apical deviation; however, no differences in bacterial microleakage was observed among the experimental groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 1 publication
3
7
0
Order By: Relevance
“…Regarding samples of Group II, (1mm from the apical foramen), there was no statistically significant difference in the mean apical foramen diameter after instrumentation when compared to its condition before instrumentation. These results also were observed in previous study (Silva et al 2016), where enlargement of the apical foramen could not be observed when root canal preparation was performed 1mm from the apical foramen. These data are confirmed by previous studies (Chugal et al 2003;Endo et al 2011), which showed that enlargement of the apical foramen improved the cleaning and filling ability during root canal therapy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding samples of Group II, (1mm from the apical foramen), there was no statistically significant difference in the mean apical foramen diameter after instrumentation when compared to its condition before instrumentation. These results also were observed in previous study (Silva et al 2016), where enlargement of the apical foramen could not be observed when root canal preparation was performed 1mm from the apical foramen. These data are confirmed by previous studies (Chugal et al 2003;Endo et al 2011), which showed that enlargement of the apical foramen improved the cleaning and filling ability during root canal therapy.…”
Section: Discussionsupporting
confidence: 89%
“…In this case, the samples were prepared using rotary nickel-titanium Mtwo instruments, showing the last file a taper of 0.04mm and a diameter close to 40 and 45 k-file.This concept is in accordance with previous studies (Benatti et al 1985;Jara et al 2018;Brandão et al 2019), which demonstrated that this type of apical enlargement does not have interference in the periapical repair. Furthermore, according to previous study, this type of apical enlargement provides better adaptation in the interface between filling material and apical foramen (Silva et al 2016).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The amount of time dedicated to chemical cleaning has been drastically reduced. It is now preferred to minimally shape the apex, with the use of 7-8% tapered and 0.20-0.25 mm of diameter instruments at the tip, in order to get a more predictable apical gutta-percha sealing to the detriment of irrigants action and possible increasing procedures [20], although other studies seem to prove the contrary [28, 29]. We aimed to revise the literature, following inclusion criteria: studies performed on that have artificial canals and extracted teeth, preventively shaped.…”
Section: Introductionmentioning
confidence: 99%